Ministry of Communications and Digital Economy | Home - Ministry of Communications and Digital Economy (Nigeria) (2020)
Ministry of Communications and Digital Economy, MCT, MOC, FMOC, FMCDE, FMOCDE, MCDE, MOCDE, Federal Ministry of Communications and Digital Economy

National Artificial Intelligence Strategy - Federal Ministry of Communications, Innovation and Digital Economy (2023)

Ministry’s Artificial Intelligence Strategy Workshop to Attract 120 Experts from Across the World - Federal Ministry of Communications, Innovation and Digital Economy (2024)